1996
DOI: 10.1111/j.1432-1033.1996.0703r.x
|View full text |Cite
|
Sign up to set email alerts
|

Blockade of the α2‐Macroglobulin Receptor/Low‐Density‐Lipoprotein‐Receptor‐Related Protein on Rat Liver Parenchymal Cells by the 39‐kDa Receptor‐Associated Protein Leaves the Interaction of β‐Migrating very‐Low‐Density Lipoprotein with the Lipoprotein Remnant Receptor Unaffected

Abstract: The nature of the liver binding site which is responsible for the initial recognition and clearance of chylomicron-remnants and P-migrating very-low-density lipoprotein (P-VLDL) is under active dispute. We have investigated the effect of the 39-kDa receptor-associated protein (RAP) on the recognition site for activated a,-macroglobulin and P-VLDL on rat liver parenchymal cells in vivo and in vitro in order to analyze whether both substrates are recognized and internalized by the same receptor system. Radiolabe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
5
0

Year Published

1998
1998
2008
2008

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 70 publications
2
5
0
Order By: Relevance
“…We found that a single dose (100 g/mL) of GST-RAP was unable to block DNA synthesis of Mv1Lu cells during an 18 h incubation. This was consistent with a report that RAP was no longer effective in blocking ␣ 2 M* association and degradation in cells after a Ͼ1 h incubation time, presumably due to efficient cellular binding and degradation of RAP under culture conditions (39). For this reason, Mv1Lu cells were incubated with various concentrations of IGFBP-3 and GST-RAP (100 g/mL) or the solvent vehicle, each (GST-RAP or the solvent vehicle) added to the culture medium hourly for 8 h. After further incubation for 10 h, DNA synthesis of the cells was determined.…”
Section: Rap Inhibits Binding Of Igfbp-3 and Tgf-␤ 1 To Cell Surface supporting
confidence: 93%
“…We found that a single dose (100 g/mL) of GST-RAP was unable to block DNA synthesis of Mv1Lu cells during an 18 h incubation. This was consistent with a report that RAP was no longer effective in blocking ␣ 2 M* association and degradation in cells after a Ͼ1 h incubation time, presumably due to efficient cellular binding and degradation of RAP under culture conditions (39). For this reason, Mv1Lu cells were incubated with various concentrations of IGFBP-3 and GST-RAP (100 g/mL) or the solvent vehicle, each (GST-RAP or the solvent vehicle) added to the culture medium hourly for 8 h. After further incubation for 10 h, DNA synthesis of the cells was determined.…”
Section: Rap Inhibits Binding Of Igfbp-3 and Tgf-␤ 1 To Cell Surface supporting
confidence: 93%
“…Although the precise mechanism of the uptake of A␤⅐apoE complex observed here is uncertain, it is possible that other apoE receptors (e.g. low density lipoprotein receptor, which is known as the major receptor for apoE) (49) were involved; RAP might have failed to efficiently block the uptake of A␤⅐lipidated apoE complex because of the relatively low affinity of other apoE receptors for RAP compared with that of LRP1 (50).…”
Section: Discussionmentioning
confidence: 88%
“…It is generally accepted, however, that for the initial liver recognition of remnants, the so-called "capture step," additional systems are needed. The initial sequestration step was suggested to involve heparan sulfate proteoglycans (5,12), the lipolysis-stimulated receptor (13)(14)(15), a TG-rich lipoprotein receptor (16,17), the asialoglycoprotein receptor (18), LPL (19), and/or hepatic lipase (20), while we also provided evidence for a specific remnant receptor (21)(22)(23) to function as an initial recognition site for remnants. However, the removal pathways of chylomicrons and their remnants remain complex, and the precise mechanism of recognition is still unclear and under debate (1-3).…”
mentioning
confidence: 82%